The Rate of Asymptomatic Bacteriuria is Similar in Term and Preterm Delivery - Amelia, Riska (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objectives: To show the prevalence of asymptomatic bacteriuria in pregnant women and to find its correlation with preterm labor. Methods: This research was performed in Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia. A total of 78 subjects joined this research. The first group consisted of 39 subjects that were having preterm delivery and the second group consisted of 39 subjects that were having term delivery. Urine analysis and culture were done in both groups. The subject was being considered to have asymptomatic bacteriuria if the urine culture showed a minimum of 100,000 bacteria/ml without any symptoms or signs of urinary tract infection. The number was then analyzed to reveal the correlation of asymptomatic bacteriuria with preterm delivery. Results: There were a significantly higher number of preterm deliveries in subjects whose age ranged between 15-19 year-old (28.20% vs 12.8%; p=0.033). While on the contrary, there was a significantly lower number of preterm delivery in subjects whose age ranged between 30-34 year-old (25.6% vs 5.12%; p=0.020).The incidence number of asymptomatic bacteriuria among all subjects is 21.79%. There was no significant difference of asymptomatic bacteriuria between preterm and a term delivery (23.07% vs 20.51%; p=0.784). Conclusions: There was no significant difference of asymptomatic bacteriuria between the subject with preterm delivery and term delivery, but the incidence of asymptomatic bacteriuria in pregnant women in this study was quite high, reaching eight times higher than those stated in other study. Thus, routine urine culture screening policy in early pregnancy still cannot be omitted, considering that asymptomatic bacteriuria can lead to pyelonephritis which can cause maternal and fetal morbidity. [Indones J Obstet Gynecol; 37-1: 8-11] Keywords: asymptomatic bacteriuria, urine analysis, urine culture, preterm delivery